Envelhecimento populacional, gratuidades no transporte público e seus efeitos sobre as tarifas na Regi\~ao Metropolitana de S\~ao Paulo - Rafael Henrique Moraes Pereira; Rafael Henrique Moraes Carvalho; Pedro Herculano G. Ferreira de Souza; Ana Amélia Camarano (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– Students, children under 4 years old and people aged 65 and over in Brazil are entitled to partial or full discount on urban trips using public transport systems. These discounts are not covered by public funding, but rather by the other service users who pay full-fare. In this study, we estimate the effects population aging in Brazil will have on public transport fares in the next four decades. We focus on the case of S\~ao Paulo Metropolitan Area (MA), the largest MA in the country. This paper is based on data from the Household Travel Survey conducted in S\~ao Paulo in 2007 and official population projections for S\~ao Paulo and Brazil for the years 2020, 2030 and 2050. Considering these different projection scenarios, we apply age-standardization methods to simulate the expected changes in the composition of public transport trips in terms of paying and non-paying passengers. According to our findings, the transformation in the age structure of S\~ao Paulo's population in the short run (2020) should have little effect on public transport trips, both in terms of total number of trips and age composition. If the current cross-subsidies scheme is maintained over the medium and long term (2030 and 2050), though, we find that the increasing share of non-paying passengers could led to an increase in full-price fare by about 10% and 20%.
Keywords: R48; R41; J11; J14; 330; aging; public transport; urban transportation; transit fare; S\~ao Paulo metropolitan area